Peran Kepala Desa Dalam Penguatan Transparansi dan Akuntabilitas Pengelolaan Dana Desa di Desa Sukarendah Kabupaten Lebak - Bambang Arianto; Titin Sopiarti (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to elaborate on the role of the village head in strengthening transparency and public accountability in the management of village funds. Strengthening aspects of transparency and accountability can make village fund distribution right on target so that it can build and empower people in rural areas. Nevertheless, in the rural context many factors influence the strengthening of transparency and public accountability such as the leadership model of the village head and participatory oversight from the community. The role of the village head greatly influences the financial governance of village funds so that they are on target, transparent, accountable and participatory. This study used a descriptive qualitative method with in-depth interviews with government officials in Sukalower Village, Lebak Regency, Banten. This study found that the role of the village head in Sukadinding village, Lebak district, was not maximized because he was unable to maximize various channels to strengthen indicators of transparency and public accountability in managing village funds.